Apetrechos de pesca determinam diferenças nas pescarias esportivas no reservatório de Itaipu - Hillesheim, Gustavo (2018)
Sports fishing tournaments have been gaining in popularity and socioeconomic importance for at least 50 years, however, in developing countries, the activity goes unnoticed by the rulers, compromising their proper management. The availability of information related to sport fishing, in its different variations and environments where it is practiced, is of relevant importance. In this way, the objective of this study was to evaluate if there are differences in the fisheries according to the socioeconomic characteristics and fishing equipments of the participants of the sport fishing tournaments of the Itaipu Reservoir. For this purpose, semi-structured questionnaires were randomly applied to the participants of 19 sport fishing tournaments of the Itaipu Reservoir, between the years of 2015 and 2016. The data obtained were transformed and submitted to a multivariate discriminant canonical analysis, aiming to identify possible groups and the variables responsible for the separation of these groups, due to the different types of tournaments (curvina and peacockbass). In all, in these tournaments, the participation of 2822 sport fishermen was registered, of which 823 were interviewed, totaling 29% of the total. There was no significant difference to characterize groups between corvina and peacockbass fishermen due to social and economic characteristics. Two groups of fishermen were trained by the fishing equipment used; in one, the fishermen used aluminum boats and live baits (curvina fishermen), in another the use of artificial baits and fiber boats are predominant (peacockbass fishermen). In this way, we conclude that the social and economic profile of the fishermen participating in the fishing tournament in the Itaipu Reservoir is high regardless of the type of tournament. There were no differences between the participants of tournaments of curvina and peacockbass. Fishing gear can differ in the type of tournament.